Analysis of Expressive Speech Acts in FWB Novel Pia Davina's Work - Helmi Seftiani; Sigit Andi Prasetya Dinata; Diana Diana (Universitas Sebelas Maret, 2021)
This research tries to describe the forms of expressive speech acts found in Pia Davina's novel